Horizontal ecological compensation as a tool for sustainable development of urban agglomerations: Exploration of the realization mechanism of Guanzhong Plain urban agglomeration in China - Yang, Yi; Zhang, Yuanyuan; Yang, Hui; Yang, Fengyi (Environmental science & policy, 2022)
Horizontal ecological compensation can promote the division of labour and collaboration among cities in urban agglomerations (UAs) and coordinate the relationship between socioeconomic development and ecological protection through payments from ecological beneficiary cities to contributor cities. However, it’s difficult to determine the compensation subjects and standard. This study uses ecological footprint (EF) and ecosystem service value (ESV) to calculate the horizontal ecological compensation standard. The ecological compensation weight is introduced to calculate the horizontal ecological compensation payment or acceptance values (HECVs) to determine the compensation subjects and objects. And we take China’s Guanzhong Plain urban agglomeration (GPUA) as an example for empirical analysis. The results show that the EF of the GPUA has the characteristics of nonequilibrium. Except for the only ecologically functional city, all other cities had ecological deficits (EDs), and the spatial distribution of the ESV in each city was significantly different, which shows that the GPUA has the conditions to establish a horizontal ecological compensation mechanism. Further research results show that higher GDP and lower ESV mean higher HECVs, key ecological function cities have the largest HECVs, and key economic development cities pay the most HECVs. This horizontal ecological compensation method regulates the relationship among stakeholders through the migration of ESV, and solves the actual problems of “who compensates whom” and “how much to compensate”. It provides strong technical support for the formulation of horizontal ecological compensation schemes for UAs in developing countries and is conducive to maintaining environmental justice and promoting the sustainable development of UAs. [Display omitted] •Proposes a method to promote regional sustainable development.•Established a horizontal eco-compensation method and framework of UAs.•Proposed the calculation method of eco-compensation standard for value conversion.•Higher GDP and lower ESV mean higher eco-compensation value.•Stakeholder participation in eco-compensation is the key to ecological balance.